PENINGKATAN KINERJA GURU DALAM PENYUSUNAN ADMINISTRASI PEMBELAJARAN MELALUI SUPERVISI AKADEMIK KEPALA MADRASAH DI MI MUHAMMADIYAH PASIR LOR KECAMATAN KARANGLEWAS KABUPATEN BANYUMAS TAHUN PELAJARAN 2018/2019 - Lily Setyowati (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2020)
Becoming a professional teacher is not a smooth path, but there are many obstacles. For example, the relationship between fellow teachers and madrasah principals is more of a bureaucratic and administrative nature than in the ministry, so that it does not encourage the building of an atmosphere and a professional academic culture among teachers. The teachers are increasingly trapped away from professional principles. They are far from books, the habit of discussing, writing, let alone doing research. Therefore, according to Suparman (2006) improvement and improvement of teacher quality related to professional competence must apply throughout his career. The purpose of this action research is to determine the extent to which madrasah head coaching through the academic supervision of madrasah principals in improving teacher performance in the preparation of learning administration. In this school action research (PTS) is carried out in 3 cycles, from the results of the action taken is proven to improve teacher performance by achieving ideal standards. From 69.28% in cycle I, it can increase to 75% in cycle II, and cycle III to 87, 14%. The results of this action research indicate that coaching through the academic supervision of madrasah principals can improve teacher performance in the preparation of learning administration with completeness reaching 100%.